Family Support System among Recovering Adolescent Drug Addicts : A Case Study - Mohd Fitri Amir Shoodi; Abu Yazid Abu Bakar; Ku Suhaila Ku Johari; Dharatun Nissa Puad Mohd Kari; Norhafizatulhusna Ismail (RedwhitePress)
The family support system gives an impact among recovering adolescent. The aim of this study is to explore the element of support system among recovering adolescent drug addicts using sandtray therapy approach. This is a case study involving four recovering adolescent at the Clinic Cure & Care Clinic, National Anti-Drug Agency, Kota Bharu, Kelantan. The thematic process was used to analize the process of group sandtray therapy and the arrangement of the miniature in the sandtray. The findings show that recovering adolescent drug addicts need family as a support system, however their families were not functioning in the prevention and recovery process. Besides that, the results show that there are three vital themesof family support system, namely: 1) family issues, 2) family structure and 3) ideal family characteristics.